Community-led research for reproductive justice: Exploring the SisterLove Georgia Medication Abortion project - Mosley, Elizabeth A.; Ayala, Sequoia; Jah, Zainab; Hailstorks, Tiffany; Dixon Diallo, Dázon; Hernandez, Natalie; Jackson, Kwajelyn; Hairston, Indya; Hall, Kelli S. (Frontiers in Global Women's Health, 2022)
Introduction: While reproductive injustice indicators are improving globally, they are worsening in the United States particularly for Black and other marginalized communities. Eugenics and obstetric violence against low-income and communities of color create well-founded distrust of sexual and reproductive health (SRH). Transformational, reparative ways of conducting SRH research are needed. Proposed Principles of Community-led Research for Reproductive Justice: Drawing on our collective experience as reproductive justice leaders, SRH researchers, and clinicians, we propose the following principles of community-led research for reproductive justice: 1) Center the marginalized community members most affected by SRH inequities as leaders of research; 2) Facilitate equitable, collaborative partnership through all phases of SRH research; 3) Honor multiple ways of knowing (experiential, cultural, empirical) for knowledge justice and cross-directional learning across the team; 4) Build on strengths (not deficits) within the community; 5) Implement the tenets of reproductive justice including structural-level analysis and the human rights framework; 6) Prioritize disseminating useful findings to community members first then to other audiences; 7) Take action to address social and reproductive injustices. SisterLove’s Community-led Georgia Medication Abortion Project: We offer the community-led Georgia Medication Abortion (GAMA) Project by reproductive justice organization SisterLove from 2018-2022 as a case study to demonstrate these principles along with the strengths and challenges of reproductive justice research. Discussion: Community-led reproductive justice research offers innovative and transformational methods for truly advancing SRH in an era of increasing policy restrictions and decreasing access to care. Yet existing funding, research administrative, and publishing systems will require structural change.